Editorial: Modern Challenges for Business and Economy in CEE Countries - Marek Szarucki (Entrepreneurial Business and Economics Review)
In recent years the phenomenon of globalisation has become an important issue, widely discussed in the academic literature. Debates explore globalisation intensity and its consequences for economies and businesses around the world. According to A.V. Rutkauskas (2013, p. 388), the processes of globalisation â€œinevitably determine the integration of countries and regions, which empowers a more economic use of natural resources, more efficient creation of new resources and the increase in the effectiveness of human resource and technology utilizationâ€. Nevertheless, in the short-range perspective, the uncontrolled processes of globalisation reveal various problems, solution of which requires extra expenditures. Thus, looking at the process of globalisation, it is possible to notice growing number of challenges that need to be coped with by governments, businesses and societies in various parts of the world (Mascarenhas, 2009). The region of Central and Eastern Europe (CEE) is not an exception from the rule. Moreover, due to different facets of globalisation and regionalisation, some challenges are similar to those in other parts of the world, although the region has its own specific problems to solve and consider on the way to success (Klich, 2013; Renko & Knezevic, 2013). Consequently, this issue of EBER concentrates on the modern challenges for organisations and countriesâ€™ economies in the region of the CEE, particularly four countries: Lithuania, Poland, Russia and Slovakia.